Evidence-based ankle pump exercise in prevention of postoperative deep-vein thrombosis in patients with lower extremity fracture (踝泵运动预防下肢骨折患者围手术期深静脉血栓的循证实践) - BAO Xiuhong (鲍秀红); ZHANG Fang (张芳); ZHU Yi (朱屹); SHAO Ye (邵烨) (中西医结合护理)
Objective To summarized the best evidence-based practice of ankle pump exercise in prevention of postoperative deep-vein thrombosis (DVT) in patients with lower extremity fracture, and to evaluate its clinical application. Methods CNKI, Wanfang, VIP, Medlive, BMJ, Cochrane library, Embase, PubMed, RNAO, ESPEN, NGC and NICE were searched for clinical practice guidelines, systematic reviews and relevant papers from August 2012 to August 2012. The best evidence was evaluated and summarized, the review items were developed for baseline assessment, and facilitating and hindering factors were analyzed. From March 2023 to July 2023, evidence was used in prevention of postoperative DVT. The pre-evidence group for baseline assessment included 154 patients, 67 nurses and 3 rehabilitation therapists from October 2022 and February 2023, while the post-evidence group for baseline assessment included 154 patients, 67 nurses and 3 rehabilitation therapists from March 2023 and July 2023. Incidence of DVT, ankle pump exercise compliance rate and averaged velocity in the common femoral vein were measured and compared between pre-evidence group and post-evidence group. Results A total of 8 articles were included, and best evidence-based practice were summarized in terms of importance of exercise, exercise frequency, holding position time and exercise intensity. After the application of best evidence practice, the incidence of DVT, the compliance rate of ankle pump exercise and the average velocity of common femoral vein were significantly different from those before the application(P＜0. 05). Conclusion By improving the implementation rate of review items and compliance rate of ankle pump exercise, evidence-based ankle pump exercise helps to reduce the incidence of DVT in patients with lower extremity fracture. (目的 总结踝泵运动预防下肢骨折患者围手术期深静脉血栓(DVT)的最佳节律并评价其应用效果。方法 系统检索中国知网(CNKI)、万方数据库(Wanfang)、维普(VIP)、医脉通、BMJ、Cochrane library、Embase、PubMed、RNAO、ESPEN、NGC、NICE、2012年8月—2022年8月发表的相关指南、系统评价和研究证据, 评价并汇总最佳证据, 制订审查条目进行基线审查, 分析促进与障碍因素。2023年3月—7月将证据应用于下肢骨折患者围手术期深静脉血栓预防中。循证证据应用前(2022年10月—2023年2月)和循证证据应用后(2023年3月—7月)分别纳入154例下肢骨折患者, 以及科室67名骨科护士及3名康复师为研究对象, 比较循证证据应用前和应用后患者DVT发生率、踝泵运动的达标率、股总静脉平均流速。结果 最终纳入8篇文献。在踝泵运动重要性、频率、停留时间和强度方面总结最佳证据。证据应用后, 患者DVT发生率较证据应用前降低, 踝泵运动达标率及股总静脉平均流速较证据应用前提升, 差异有统计学意义(P＜0. 05)。结论 运用最佳证据指导下肢骨折围手术期深静脉血栓预防, 可提高各审查指标的执行率和患者踝泵运动的达标率, 从而降低DVT的发生风险。)